O-015 Angiographic features help predict outcome after γ knife radiosurgery for the treatment of pediatric arteriovenous malformations. (4th July 2012) - Sheth, S; Potts, M; Louie, J; Sneed, P; Fullerton, H; McDermott, M; Young, W; Gupta, N; Dowd, C; Hetts, S
Abstract : Background: Gamma Knife radiosurgery (GKRS) is an option in the treatment of pediatric arteriovenous malformations (AVMs), especially for AVMs in eloquent locations or patients with good functional status. Prior studies have indicated that lower target volumes and higher prescription doses are associated with improved obliteration rates. Certain angiographic features including maximal diameter, diffuse border, and venous drainage patterns have also been shown to have n influence on rate of obliteration after GKRS. 1 2 3 Methods: We retrospectively reviewed all pediatric patients age ≤18 treated with GKRS for an AVM between 2000 and 2010 at our institution. Angiographic features based on pre-treatment angiography were prospectively recorded in a standardized manner and scored by experienced neuroradiologists. Results: Between 2000 and 2010, 41 children (23 boys and 18 girls) underwent GKRS for an AVM. Follow-up information was available for 39 patients with 3-year angiographic follow-up in 22. Mean age at time of treatment was 13.5±3.5 years. Two patients had a Spetzler-Martin grade (SMG) II, 23 had grade III, 12 had grade IV, and 4 had grade V. The mean target volume for GKRS was 9.2±10.2 cm 3 while the median prescription dose of radiation was 18Gy (range 16–20 Gy). 13 patients underwent staged GKRS. Among the 22 patients with 3-year angiographic follow-up, complete obliteration was observed in 9 (40.9%), while 12 (54.5%) showed a partial response. Only one patient had no response. Prescription dose was significantly correlated to angiographic response (p=0.046, logistic regression), with a dose ≥18 Gy being associated with a 75% complete obliteration rate compared to 27.2% in patients treated with <18 Gy. Smaller AVMs were more likely to have complete response to treatment, though this finding did not achieve statistical significance. Presenting with hemorrhage, vs seizure and headache, correlated with improved response rate with 8/9 complete responders presenting with hemorrhage vs 5/12 of the partial or non-responders. Age and SMG were not associated with response rate. We then examined the influence of angioarchitectural features on the rate of response to GKRS. Factors found to significantly increase the chance of complete obliteration included smaller maximal diameter (mean of 2.2 cm in obliterated group vs 3.5 cm in group with residual AVM), fewer draining veins (1 vs >1), and fewer draining veins reaching a sinus (1 vs >1). Factors that did not have an influence on response rate included diffuse borders of AVM, having only deep venous drainage, venous ectasia, venous reflux, presence of any aneurysm, embolization prior to GKRS, and arterial inflow through anterior vs. posterior circulation. Conclusion: There is a growing literature that GKRS is an effective treatment for pediatric AVMs. Our study finds that in addition to AVM volume and prescription dose, certain angioarchitectural features play a role in the rate of obliteration after treatment with GKRS. Smaller AVMs with fewer draining veins and fewer draining veins reaching a sinus had favorable outcomes. Competing interests: None. References: 1. Chang et al. J Neurosurg 2000;93 (Suppl 3):96–101. 2. Kano et al. J Neurosurg Pediatrics 2012;9: 1–10. 3. Yeon et al. Childs Nerv Syst 2011;27 :1109–19.